Calcium Channel Blocker Use and the Risk for Prostate Cancer: A Population‐Based Nested Case‐Control Study. Issue 6 (17th April 2019) - Rotshild, Victoria; Azoulay, Laurent; Feldhamer, Ilan; Perlman, Amichai; Muszkat, Mordechai; Matok, Ilan
Abstract : Introduction: Calcium channels play a significant role in the regulation of cell proliferation and apoptosis. This study investigates associations between calcium channel blocker (CCB) use and the incidence of prostate cancer (PCa). Methods: A nested case‐control study was conducted using the Clalit Health Services database. We formed a population‐based cohort of patients who were prescribed their first antihypertensive agent between 2000 and 2014. For each newly diagnosed PCa case in the cohort, 10 controls were matched by age, calendar year of cohort entry, and duration of follow‐up. Multivariate conditional logistic regression analyses were used to evaluate the odds ratios (ORs) of PCa among CCB users compared with users of other antihypertensive drugs. Results: We identified 4346 patients with newly diagnosed PCa during the median follow‐up of 5.3 years. The exposure to CCBs was associated with a slight increase in risk for PCa (OR 1.10, 95% confidence interval [CI] 1.02–1.18) when compared with non‐CCB antihypertensive drugs. In secondary analyses, evidence was found of a duration‐response relationship, with the association for PCa increasing by 27% for every 10‐year increment of CCB use (OR 1.27, 95% CI 1.04–1.56). Conclusions: The results of this large population‐based study indicate a modest but significant increase in the risk of PCa among CCB users, and the risk increases with duration of use.